2014 IEEE International Symposium on Medical Measurements and Applications (MeMeA) 2014
DOI: 10.1109/memea.2014.6860048
|View full text |Cite
|
Sign up to set email alerts
|

Experimental comparison of orientation estimation algorithms in motion tracking for rehabilitation

Abstract: This paper presents the experimental comparison of data fusion algorithms for human motion tracking in rehabilitation, using Inertial Measurement Units. Three algorithms for orientation estimation, taken from the scientific literature in the field, have been selected and their capability of accurately tracking the angle of a selected joint has been evaluated. In particular, two phases of experimental analysis have been carried out. The former, in laboratory, was directed to verify the capability of the algorit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…IMUs provide raw acceleration, angular rate and magnetic field data that need to be fused together to obtain a sole, optimal estimate of orientation. Diverse algorithms have been proposed in the literature to that end, including Kalman filters [ 63 ], least squares filters [ 64 ] or Gaussian particle filters [ 65 ], among many others [ 66 , 67 ]. The mDurance system particularly implements a recent technique, Madgwick's algorithm [ 68 ], which outperforms most existing approaches in terms of implementation complexity, sampling rate requirements and computational needs.…”
Section: Mdurance: a Novel System For Trunk Endurance Assessmentmentioning
confidence: 99%
“…IMUs provide raw acceleration, angular rate and magnetic field data that need to be fused together to obtain a sole, optimal estimate of orientation. Diverse algorithms have been proposed in the literature to that end, including Kalman filters [ 63 ], least squares filters [ 64 ] or Gaussian particle filters [ 65 ], among many others [ 66 , 67 ]. The mDurance system particularly implements a recent technique, Madgwick's algorithm [ 68 ], which outperforms most existing approaches in terms of implementation complexity, sampling rate requirements and computational needs.…”
Section: Mdurance: a Novel System For Trunk Endurance Assessmentmentioning
confidence: 99%
“…As an example, accelerometer data could be logged, and from that, stride time could be extracted using the methodology as described in [17]. Also, there has been experimental comparison of orientation estimation algorithms in motion tracking for rehabilitation [18] that could be incorporated. Finally, external sensor data could be fused with data collected from the handheld device [19].…”
Section: B Stealth Data Acquisition and Algorithmsmentioning
confidence: 99%
“…Patient's posture was intended to be reconstructed from sensed data by a dedicated server, Posture Reconstruction Server (PRS), installed at medical facilities, running multiple instances of an orientation estimation algorithm at a time. Three of the most efficient algorithms for orientation estimation proposed in research were compared and found capable of meeting the accuracy requirements expected in rehabilitation applications [6]. More precisely, it turned out that the solution based on gradient descent algorithm (GDA) [7] is the best at performing joint angular measurement, both under static and dynamic conditions, for the daily-life gestures recreated.…”
Section: Introductionmentioning
confidence: 99%